Concept of numbers and cognitive poetics in the story Lawrence Sona «area of the triangle». (Journal of Oriental Studies, 2016)
The article deals with accentuation obsessional images, characters of Korean immigrants in Kazakhstan, contributing to the preservation of national identity and successful adaptation to the alien society.
Keywords: symbolism; obsessive discourse; obsessional accentuation; national identity; the concept of numbers